Esther Herrera Z. (ed.), Temas de fonética instrumental. El Colegio de México, México, 2001; 108 pp. (Estudios del Lenguaje, 5). - Chávez Peón, Mario E. (El Colegio de México, 2002)
Se reseñó el libro: Temas de fonética instrumental.